MODELING OF DIOCTAHEDRAL 2:1 PHYLLOSILICATES BY MEANS OF TRANSFERABLE EMPIRICAL POTENTIALS - Sainz-Diaz C.I.; Hernández-Laguna A.; Dove M.T. (My University, 2001)
Dioctahedral 2:1 phyllosilicates with different interlayer charge have been studied theoretically by using transferable empirical interatomic potentials. The crystal structures of pyrophyllite, muscovite, margarite, beidellite, montmorillonite, and different smectites and illites have been simulated. The interatomic potentials were able to reproduce the experimental structure of phyllosilicates with high, medium and low interlayer charge. The calculated structures are in agreement with experiment for the main structural features of the crystal lattice. The effect of the cation substitution in the octahedral and tetrahedral sheets on the structural features has been also studied. Good linear relationships have been found, and the calculated effects are consistent with experimental results. Some unknown structural features of the crystal structures of clays are predicted in this work.